PEMAHAMAN FAKTA SEJARAH NASIONAL INDONESIA PADA SISWA SMU DITINJAU DARI KEMAMPUAN GURU DALAM PEMBELAJARAN DAN PENGALAMAN MENGAJAR GURU SEJARAH - Sukarno, MH (MIIPS, 2008)
The main purpose of the study is to examine the effect of the teacher?s experiences and competencies in teaching on the students? understanding of Indonesian Nasional Historical Facts. In specific, the purposes of the study are to examine: (1) the differences of the effect of teacher?s experiences in history teaching who had high level competencies from those having the medium and the lower ones on students? understanding of Indonesian National Historical Facts; (2) the differences of the effect of teacher?s experiences in history teaching who had the high level the competencies from those having the medium and the lower ones; and (3) the interaction of the effect of the history teachers? experiences and competencies towards the Students? understanding of Indonesian National Historical Facts.The method of this Study is an ex post facto one using 3x3 factorial design. The population of the Study were 2229 male and female students of the quarter 2 of the second grade akademic year of the State Senior High Schools Sukoharjo. The sample for the study included 560 students which were taken by using cluster random sampling technique. The results of the study are: (1) there is a significant effect difference of the history teacher?s teaching competencies on the students? understanding of Indonesian National Historical Facts; the obtained FOJ is 5,3 which is higher than F.(0.95:2,55)= 3.00 on the significance level 0,05; (2) there is a different effect of the history teacher?s teaching experiences on the students? understanding of the Indonesian National Historical Facts; the obtained FoG= 42,3 which is higher than F(0,95:2.55) = 3,0. significance level 0.05; and (3) there is a significant interaction between the history teacher?s teaching experiences and their teaching competencies on the students? understanding of the Indonesian National Historical Facts; the obtained FoJ is 26,1 which higher than F.(0.95-4,551) = 2,37., at the significance level of 0.05.